2022
DOI: 10.1177/09636897221108192
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199-3p Suppressed Inflammatory Response by Targeting MECP2 to Alleviate RTX-Induced PHN in Mice

Abstract: Varicella zoster virus–induced postherpetic neuralgia (PHN) can be alleviated by limited medications with serious side effects. This study aims to investigate the underlying molecular mechanism of miR-199-3p in mediating PHN in mice. 293T cells were transfected with miR-199-3p vectors (mimic/inhibitor). The target relationship between miR-199-3p and MECP2 was confirmed using luciferase reporter assay. PHN mouse model was established by TRX injection. Animal behaviors were evaluated using Hargreaves test and Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…This may be due to species variability or different cell type responses. Other miRNAs, such as miR-124, miR-206-3p, miR-1a-3p, miR-134, miR-23a-3p, miR-199, miR-486-5p, miR-210-3p, and miR-185, showed differential expression after antigenic stimulation and are known to be involved in immune regulation, inflammation, osteogenic differentiation, angiogenesis, and apoptosis ( Li et al, 2016 ; Huang and Zhu, 2018 ; Zhao et al, 2018 , 2023 ; Chen et al, 2019 , 2023 ; Chen J. X. et al, 2020 ; Ghafouri-Fard et al, 2021 ; Yang et al, 2021 ; Zhang Z. et al, 2021 ; Wang et al, 2022 ; Castaño et al, 2023 ; Dong et al, 2023 ; Li and Li, 2023 ; Liu et al, 2023 ; Ma et al, 2023 ; Su et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to species variability or different cell type responses. Other miRNAs, such as miR-124, miR-206-3p, miR-1a-3p, miR-134, miR-23a-3p, miR-199, miR-486-5p, miR-210-3p, and miR-185, showed differential expression after antigenic stimulation and are known to be involved in immune regulation, inflammation, osteogenic differentiation, angiogenesis, and apoptosis ( Li et al, 2016 ; Huang and Zhu, 2018 ; Zhao et al, 2018 , 2023 ; Chen et al, 2019 , 2023 ; Chen J. X. et al, 2020 ; Ghafouri-Fard et al, 2021 ; Yang et al, 2021 ; Zhang Z. et al, 2021 ; Wang et al, 2022 ; Castaño et al, 2023 ; Dong et al, 2023 ; Li and Li, 2023 ; Liu et al, 2023 ; Ma et al, 2023 ; Su et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that miR-29-enriched exosomes originate from stem cells and alleviate proinflammatory responses in an osteoarthritis in a rat model (Le et al, 2016). Similarly, miR-199-3p overexpression attenuated TRX-induced PHN by targeting MECP2 in mice (Wang et al, 2022). ExomiR-181c-5p was incorporated by microglial cells and prevented inflammatory substances from being released.…”
Section: Emerging Role Of Exosomal Mirnas In Neuropathic Pain Managementmentioning
confidence: 97%
“… 121 Similarly, miR-199-3p overexpression in mice attenuated postherpetic neuralgia induced by TRX by targeting MECP2. 122 Microglial cells incorporated exomiR-181c-5p, which prevented the release of inflammatory substances. Intrathecal treatment with exomiR-181c-5p in CCI rats reduced neuroinflammatory symptoms and neuropathic pain.…”
Section: The Emerging Role Of Exosomal Rnas In Neuropathic Painmentioning
confidence: 99%